#### Answer

$(2x^3+2)(3x^3+5)$

#### Work Step by Step

$3x^6+11x^3+10=3x^6+6x^3+5x^3+10=3x^3(2x^3+2)+5(2x^3+2)=(2x^3+2)(3x^3+5)$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$(2x^3+2)(3x^3+5)$

$3x^6+11x^3+10=3x^6+6x^3+5x^3+10=3x^3(2x^3+2)+5(2x^3+2)=(2x^3+2)(3x^3+5)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.